PRAKTIK HUTANG PIUTANG BAJU BEKAS (LELONG ) DALAM KARUNG DIBAYAR DENGAN GABAH DALAM PERSPEKTIF HUKUM ISLAM - Muhammad Rio (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
In the implementation of the practice of debt receivables from used clothes in sacks paid with grain. In the perspective of Islamic law in Sumber Harapan Village, Sekajau Subdistrict, it can be said that the practice is not in accordance with Islamic law because there is one condition that has not been fulfilled, namely, Ijab qabul because the agreement is only on the part of the giver. debt. Meanwhile, other conditions have been met, including: the person giving the debt is the customer who always buys in sacks. while the object or item owed is in the form of used clothes (Lelong) that have been damaged and are sometimes far from being suitable for resale.